Omnidirectional Phase Matching In Zero-Index Media - Gagnon, Justin (Université d'Ottawa / University of Ottawa, 2021)
Since its inception, the field of nonlinear optics has only increased in importance as a result of a growing number of applications. The efficiency of all parametric nonlinear optical processes is limited by challenges associated with phase-matching requirements. To address this constraint, a variety of approaches, such as quasi-phase-matching, birefringent phase matching, and higher-order-mode phase matching have historically been used to phase-match interactions. However, the methods demonstrated to date suffer from the inconvenience of only being phase-matched for one specific arrangement of beams, typically co-propagating along the same axis. This stringency of the phase-matching requirement results in cumbersome optical configurations and large footprints for integrated devices. In this thesis, we show that phase-matching requirements in parametric nonlinear optical processes may be satisfied for all orientations of input and output beams when using zero-index media: a condition of omnidirectional phase matching. To validate this theory, we perform experimental demonstrations of phase matching for five separate FWM beam configurations to confirm this phenomenon. Our measurements constitute the first experimental observation of the simultaneous generation of a forward- and backward-propagating signal with respect to the pump beams in a medium longer than a free-space optical wavelength, allowing us to determine the coherence length of our four-wave-mixing process. Our demonstration includes nonlinear signal generation from spectrally distinct counter-propagating pump and probe beams, as well as the excitation of a parametric process with the probe beam's wave vector orthogonal to the wave vector of the pump beam. By sampling all of these beam configurations, our results explicitly demonstrate that the unique properties of zero-index media relax traditional phase-matching constraints, and provide strong experimental evidence for the existence of omnidirectional phase matching in zero-index media. This property can be exploited to facilitate nonlinear interactions and miniaturize nonlinear devices, and adds to the established exceptional properties of low-index materials.
Keywords: Zero-index; Phase matching; Nonlinear Optics; Four-wave mixing; Nanophotonics; Dirac-cone; Metamaterials; Photonic crystal; Omnidirectional; Nanofabrication; Photonics; ENZ; ENZ material; MNZ; MNZ material; EMNZ; EMNZ material; Nonlinear interaction; Coherence Length; Physics; Optics; PBG; Dispersion